2019
DOI: 10.1080/14616696.2019.1660392
|View full text |Cite
|
Sign up to set email alerts
|

Low education, high job quality? Job autonomy and learning among workers without higher education in Scandinavia, the United Kingdom and Ireland

Abstract: Since reforms implemented in 1994, vocational education and training (VET) in Norway has been integrated and standardized as part of upper-secondary education. When young people enter upper-secondary education at the age of 15 or 16, they can choose either a vocational programme or a general academic programme. The standard model in vocational programmes is 2 years of school-based education, followed by 2 years of apprenticeship training. However, in practice, only a minority follow the standard route and ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…Moreover, education has a relationship with individuals’ chance of working on high quality jobs. For example, research has shown that compared with those with higher education, workers with lower education are less likely to work on high‐quality jobs featuring learning opportunities, fair compensation, and job autonomy (e.g., Aspøy, 2020; Wicht et al., 2019). When organizations do provide such kinds of high‐quality jobs using HIWPs, older workers with a lower educational level are more likely to take the opportunity and more positively react to HIWPs.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Moreover, education has a relationship with individuals’ chance of working on high quality jobs. For example, research has shown that compared with those with higher education, workers with lower education are less likely to work on high‐quality jobs featuring learning opportunities, fair compensation, and job autonomy (e.g., Aspøy, 2020; Wicht et al., 2019). When organizations do provide such kinds of high‐quality jobs using HIWPs, older workers with a lower educational level are more likely to take the opportunity and more positively react to HIWPs.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…For example, Dong et al (2021) found that employees with long working hours benefited more from job autonomy. Aspøy (2020) found that employees without higher education exercised less job autonomy. Ng and Feldman (2015) found that older workers experienced greater levels of the positive outcomes of job autonomy.…”
Section: Resultsmentioning
confidence: 99%